Tyrosine kinase activity of CD4-associated p56lck may not be required for CD4-dependent T-cell activation. - Collins, T L (1993)
The lymphoid-specific tyrosine kinase p56lck (Lck) is critical for the development and activation of T lymphocytes, and Lck kinase activity has been implicated in both T-cell antigen receptor/CD3- and CD4-mediated signaling. CD4-dependent T-cell activation has been demonstrated to be dependent upon the association of CD4 with Lck. To examine the role of the kinase activity of Lck in CD4-dependent T-cell activation, we have generated several kinase-deficient mutants of Lck. When transfected into CD4+ murine T-cell hybridoma cells, these mutants cause approximately 90% diminution in CD4-associated Lck kinase activity. Specifically, upon CD4 crosslinking there is decreased Lck autophosphorylation and decreased phosphorylation of an exogenous substrate. When CD4 is crosslinked to the T-cell antigen receptor-CD3 complex, decreased phosphorylation of associated substrates is also observed. In spite of this striking inhibition of Lck kinase function, cells expressing the kinase-deficient mutants demonstrate normal or enhanced CD4-dependent antigen responsiveness. These data demonstrate that the level of Lck kinase activity does not correlate with its CD4-associated function and suggest that the kinase activity of Lck may not be required for CD4-mediated signaling.